Epidemiology and Clinical Features of Arterial Hypertension in Patients with Type 2 Diabetes Mellitus. Literature Review - G. A. Ignatenko; A. E. Bagriy; A. V. Prikolota; O. A. Prikolota; E. S. Mykhailichenko; I. A. Arshavskaya; K. E. Mogilevskaya (Архивъ внутренней медицины)
Hypertension and type 2 diabetes mellitus are often combined and mutually enhance the adverse effect on vascular and renal prognosis. Hypertension is present in about 50 % of patients with type 2 diabetes, and diabetes, in turn, is detected in about 20 % of people with hypertension. The risk of developing hypertension in patients with type 2 diabetes is 2-2.5 times higher than in people without diabetes; the presence of hypertension increases the risk of type 2 diabetes by the same number of times. Hypertension and diabetes mutually burden each other: on the one hand, the presence of hypertension significantly increases the likelihood of developing diabetic macro- and microvascular complications (including diabetic nephropathy and retinopathy); on the other hand, type 2 diabetes, as a classic independent cardiovascular risk factor, increases the risk of complications inherent in hypertension by about 2 times Careful treatment of diabetes with maintenance of target values of glycemia for a long time may be associated with a decrease in the likelihood of developing hypertension by 24 % compared with less adequate control of glycemia. Hypertension in type 2 diabetes may have a number of features that distinguish such patients from the general population of people with hypertension. Such features include a higher proportion of isolated systolic hypertension and resistant hypertension, certain types of circadian rhythm disorders of blood pressure (categories “non-dipper” and “night-peaker”), frequent combination with albuminuria, frequent high salt sensitivity and volume-dependent nature of hypertension, and others.